Zaangażowanie muzeum w proces komunikowania o zmianie klimatu - Nieroba, Elżbieta (Zbiór Wiadomości do Antropologii Muzealnej, 2019)
In this paper I addressed the issue of the engagement of museums in climate change. The problem of climate change is so important in the current social context that, despite its difficult political connotations, it cannot be ignored by museums, especially if we consider a museum as an element of a public sphere. Climate change is a challenge in 21st century. Climate change will present challenges that are of long-term nature, multidimensional and global phenomenon. It could impact directly on museums. I assume museums can provide a safe place for dialogue around climate change. Museums can also inform publics about the science of climate change and help to equip people with knowledge, shape their attitudes and behaviour, and strengthen the mechanism of participation. Potential barriers in effective communication could be the problem of uncertainty of our knowledge about climate change, scientific discourse in the process of communication and getting visitors involved.